Pengaruh Ukuran Perusahaan, Pertumbuhan Aset, Struktur Aset, Tingkat Utang, dan Likuiditas Terhadap Profitabilitas - Muhamad Naufal Lukman Hakim; Eny Purwaningsih (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Company size, asset growth, asset structure, debt ratio, and liquidity are the variables analyzed in this study to determine their impact on profitability. Companies listed on the Indonesia Stock Exchange (IDX) that produce consumer goods from 2019 to 2023 are the objects of this study. Several factors are considered independent variables, including company size (natural logarithm of total assets), asset growth rate, asset structure (ratio of fixed assets to total assets), debt level (Debt to Asset Ratio), and liquidity ratio (Current Ratio). ROE is used as the dependent variable to measure profitability. The study sample consists of 30 companies with five years of data, resulting in a total of 150 observations. However, an outlier occurred, resulting in 28 companies with a total of 140 observations. Multiple linear regression was used in this study. The test findings show that all five independent factors significantly influence profitability simultaneously. While asset structure, debt level, and liquidity have a negative and significant impact, only asset growth has a positive and significant impact. There is no significant impact of company size. This study provides a clear understanding of the role of financial structure and asset management in improving corporate profitability, which is beneficial for both management and investors.